2017
DOI: 10.1002/suco.201500216
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the mechanical properties of basalt fiber‐reinforced concrete

Abstract: This paper presents an experimental investigation of how varying the volume fraction of chopped basalt fibers affects the mechanical properties of fiber‐reinforced concrete (FRC). The fiber content is varied in the range of 0–2%. The main parameters investigated are workability, compressive strength, splitting tensile strength, flexural strength, and flexural toughness. Test results showed that the compression strength of concrete decreased marginally with the addition of basalt fibers in comparison with plain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(47 citation statements)
references
References 21 publications
1
46
0
Order By: Relevance
“…Hasan Katkhuda and their fellows [30] examined that adding of 18mm basalt fiber in plain concrete will increase in flexural strength while same will give max increase of flexural strength in recycled and treated recycled concrete aggregate by adding 1.5% basalt fiber. Shruti Jalasutram and their fellows [31] revealed that adding 12.7mm and 2% basalt fiber in concrete will increase max 75% of flexural strength of concrete. Wang Jun and their fellows [32] conclude that adding 30mm and 0.25% basalt fiber in concrete will give a min increase of 0.53% flexural strength.…”
Section: Flexural Strengthmentioning
confidence: 98%
See 2 more Smart Citations
“…Hasan Katkhuda and their fellows [30] examined that adding of 18mm basalt fiber in plain concrete will increase in flexural strength while same will give max increase of flexural strength in recycled and treated recycled concrete aggregate by adding 1.5% basalt fiber. Shruti Jalasutram and their fellows [31] revealed that adding 12.7mm and 2% basalt fiber in concrete will increase max 75% of flexural strength of concrete. Wang Jun and their fellows [32] conclude that adding 30mm and 0.25% basalt fiber in concrete will give a min increase of 0.53% flexural strength.…”
Section: Flexural Strengthmentioning
confidence: 98%
“…Hasan Katkhuda and their fellows [30] conclude that increase in compressive strength while adding basalt fiber of 18mm length in concrete, but while replacing aggregate with recycled & treated recycled concrete aggregate it gives an increase in compressive strength when adding 0.5 & 1%, while decreases when adding basalt fiber 0.1 & 1.5%. Shruti Jalasutram and their fellows [31] examined that 12.7mm length and 0.5,1,1.5,2% of basalt fiber added in concrete it gives decrease in compressive strength 0, 2.6, 2.08, 2.86% respectively. Wang Jun and their fellows [32] Revade and their fellows [33] added 0.5, 1.0, 1.5% basalt fiber of 12mm length results increase in compressive strength 13.27, 11.15, 7.06% respectively.…”
Section: Hardened Concrete Properties: a Compressive Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…Because crimped wire mesh is being used as much as reinforcing bars in walls and slabs, an experimental research using crimped wire mesh is highly important and necessary (Figure ). Particularly, there has been only a few research on wire mesh‐reinforced concrete (WMRC) with steel fibers, which has shown potential to improve the mechanical properties of concrete such as ductility, toughness, and bond strength . Therefore, this paper deviates from the evaluation of impact resistance of concrete which has largely taken a traditional view of material, but is an outcome of an experimental research project in evaluating the impact resistance of concrete conditioning on the presence or absence of crimped wire mesh, evaluating the impact resistance of steel fiber‐reinforced concrete (SFRC), and gauging the impact resistance of wire mesh‐ and steel fiber‐reinforced concrete panels.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, there has been only a few research on wire mesh-reinforced concrete (WMRC) with steel fibers, which has shown potential to improve the mechanical properties of concrete such as ductility, toughness, and bond strength. 4,[7][8][9] Therefore, this paper deviates from the evaluation of impact resistance of concrete which has largely taken a traditional view of material, but is an outcome of an experimental research project in evaluating the impact resistance of concrete conditioning on the presence or absence of crimped wire mesh, evaluating the impact resistance of steel fiber-reinforced concrete (SFRC), and gauging the impact resistance of wire mesh-and steel fiber-reinforced concrete panels. Specifically, this study aims to evaluate (a) the effect of the presence or absence of Discussion on this paper must be submitted within two months of the print publication.…”
Section: Introductionmentioning
confidence: 99%